2020
DOI: 10.7759/cureus.10922
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Modalities for Calcified Coronary Artery Disease: A Review Article Comparing Novel Intravascular Lithotripsy and Traditional Rotational Atherectomy

Abstract: The coronary artery calcium score is considered the most useful marker for predicting coronary events. The high score reflects heavy calcification in the vessel, which is more challenging to treat with the percutaneous intervention (PCI). To prepare this type of heavily calcified lesion intravascular lithotripsy (IVL) technology can be used prior to PCI, which is based on the concept of converting electrical energy into mechanical energy. It harmlessly and selectively disrupts both the shallow and deep deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Very tight calcified lesions may resist dilatation at low balloon inflation pressures or rupture at high pressures. This causes high rates of procedural complications and, consequently, poor clinical outcomes [ 6 ]. Recent therapeutic calcium debulking techniques used to overcome CAC can be categorized into two groups: non-balloon (rotational, orbital, and laser coronary atherectomy) and balloon-based technologies (high-pressure/ultra-high-pressure non-compliant balloon, scoring/cutting balloons, shockwave IVL balloon).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very tight calcified lesions may resist dilatation at low balloon inflation pressures or rupture at high pressures. This causes high rates of procedural complications and, consequently, poor clinical outcomes [ 6 ]. Recent therapeutic calcium debulking techniques used to overcome CAC can be categorized into two groups: non-balloon (rotational, orbital, and laser coronary atherectomy) and balloon-based technologies (high-pressure/ultra-high-pressure non-compliant balloon, scoring/cutting balloons, shockwave IVL balloon).…”
Section: Discussionmentioning
confidence: 99%
“…Derived from lithotripsy technology employed to treat nephrolithiasis [ 8 ], the shockwave IVL system has also proved to be beneficial in treating CAC. Compared to the aforementioned conventional approaches, the shockwave IVL system requires minimal training and provides excellent outcomes of luminal widening, successful stent implantation, and reduced risk of major adverse cardiovascular events [ 6 ]. These observations are noted in our case, too.…”
Section: Discussionmentioning
confidence: 99%
“…Four patients received a drug-coated balloon. No significant differences were found in operation time and success rate among the low (<23), intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and severe (>32) CAD groups based on SYNTAX score stratification (P > 0.05). Two subacute thrombosis cases each were reported perioperatively, during hospitalization, and at the 1-month follow-up.…”
mentioning
confidence: 87%
“…The European and American guidelines state that the anatomical SYNTAX score is an essential tool that could help clinicians choose the most appropriate revascularization strategy for patients with complex CAD-PCI or coronary artery bypass graft (CABG) surgery (15,16). Based on the anatomical severity of CAD, the patients can be categorized as low (<23), intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (>32) category according to the SYNTAX score. It was found that low-and intermediatecategory patients have similar long-term outcomes regardless of the revascularization strategy implemented (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary IVL (using the Shockwave IVL (S-IVL) (shockwave medical, Ins., Santa Clara, CA, USA), was approved in 2021. [24] IVL utilizing localized pulsatile sonic pressure waves at low pressure provides a novel approach for lesion preparation of severely calcified plaques. Electrohydraulic waves produced by IVL can disrupt subendothelial calcification, successfully fracturing circumferential calcium [25,26] [Table 2].…”
Section: Impact Of Cac On Pci Outcomesmentioning
confidence: 99%